A case-control study of chronic otitis media and acculturation among the Yukon-Kuskokwim Delta Eskimos. - Zurita, R. Beatriz (1992)
Chronic otitis media (COM) is highly prevalent among Eskimo children, as well as in other groups characterized by low socio-economic status, living in crowded conditions, having poor sanitation, and receiving no or inadequate medical care. This dissertation examined the association between COM and selected social, cultural, economic and physical environmental factors: language spoken at home; adult education and occupation; income; distance from the city of Bethel, household crowding, and adequacy of human waste disposal. The purpose was to improve understanding of the epidemiology of COM with respect to these factors. The study also attempted to test a model of acculturative stress, that increased stress leads to an increased burden of disease. This test had limited success due to the constraints imposed by the nature of the secondary data analysis. Twenty-one percent of the Eskimo children below the age of eight years had COM. The statistically significant predictors of COM were age, educational achievement of a female resident of the household, government supplemental income, distance from the city of Bethel, and household crowding. Additional variables that achieved marginal significance were language spoken at home and family income. COM among children was slightly more prevalent in males; among 3 and 4 year olds; the Bethel children; very young children in large crowded households; poor children from families without income supplements; those living with females who have some formal education; and the monolingual Yup'ik-speakers. The variables that were not significant risk factors for COM were the male household occupant's education, male or female occupant's occupation, and type of waste disposal. The implications of these findings for local health programs and Native health policy are discussed, together with suggestions for future research. For example, interventions are suggested for reducing the prevalence of COM and its burden among the Y-K Delta Eskimos. Strategies within the health care system ...